Understanding and combating tuberculosis - Russell, David (Henry Stewart Talks, 2021)
Introduction to tuberculosis and immune control, Macrophage subsets in the lung, Transcriptional profiling of pathogen and host, Immunometabolism in TB infection and disease control, Novel drug screening platforms and new anti-TB drugs, Investigation of the HIV-1/TB interplay, Biology of HIV-1 infection of macrophages